environmental values training from the perspective of sustainable human development (Revista Electrónica REDINE, 2018)
This dissertation was aimed to create spaces for reflexive training for the formation of environmental values ​​from the perspective of sustainable development, due to the situation that presents humanity with the increasing environmental deterioration, it arises from the participatory diagnosis carried out in the Bolivarian school Esteban RASQUIN located in the Alto de Escuque in Trujillo state. It supported the sociocritic paradigm, qualitative methodology is assumed as participatory action research method, since phases: diagnosis, planning, implementation and reflection applied throughout the development of research. We conclude that we are all responsible for transforming our context as long as we value ours and all that mother nature gives us for the benefit of all who yearn to achieve balance and harmony between human beings and the environment.
Keywords: training; values; initial education; sustainable human development; environmental education